Pengembangan Multimedia Presentasi Interaktif Berbasis Canva Menggunakan Model Problem Based Learning Materi Bagian Tubuh - Tumbuhan - Tania Elsa Rahayu; Isa Ansori (Postgraduate, University of Mataram, 2025)
Science learning in primary schools still faces challenges in improving student learning outcomes. One solution is the use of interactive learning media that utilise technology and appropriate learning models. Research at SDN Bringin 01 Semarang City developed an interactive multimedia presentation using the Problem Based Learning (PBL) model for science subjects. The research method used Research and Development (R&D) with the ADDIE model. The results showed that the multimedia developed was successful and feasible to use, with a feasibility assessment from media experts of 91.5% and material experts of 89.5%. The use of this multimedia is effective in improving student learning outcomes, with an increase of 25.5% and a significant difference between before and after use. The N-Gain test showed a high criterion of 0.72. Thus, PBL-based interactive multimedia presentations can be a solution to improve the quality of science learning in elementary schools. The PBL model itself has been proven effective in improving students' critical thinking and problem-solving skills Class IV of SDN Bringin 01 Semarang City, totalling 28 students.